O ginásio municipal e o ensino secundário em Fortaleza: percursos históricos e itinerário social (1949-1971) - Ricarte, Erbenia Maria Girão (2022)
This study seeks to understand the historical, pedagogical and social trajectory of the first municipal school in the city of Fortaleza, from its creation and evolution into an institution that marked a time, an era and the lives of many teachers and students, as well as the entire society in Fortaleza, in the middle of the 20th century, between 1949, the date of its creation, and the beginning of the 1970s, a time when education in Ceará was going through a precarious and difficult phase and that school struggled to remain at the municipal level. As a theoretical contribution, we will have reflections and dialogues in studies in the History of Education (Saviani, 2007), which covers, among other dimensions, the history of school institutions, whose most exponent scholars are Paolo Nosella and Ester Buffa (2008), understanding memory as an important methodological tool in human sciences research (Le Goff, 2013), based on Durkheim (2014) with regard to education as an eminently social fact, as well as also based on Haidar (1972) with regard to organization of secondary education in Brazil and in Sousa (1966), about the school organization in Fortaleza and António Bencostta (2005), that it is important to recognize schools as a physical space, among other authors who supported the study presented here. From an approach in the history of education, we will seek to research through the narratives of former students, former teachers and employees, elements of the history and memory of the referred school institution regarding the social transformations from its emergence in the municipal scenario. To organize the research, we divided the study into four stages: 1) reading the bibliography concomitantly with the investigation of the location of former professors and former students; 2) Interviews with these actors of the institution; 3) Visit to the buildings that gave life to that institution, public archives and the city council; 4) cataloging and data analysis. In this way, we understand that the research aims to rescue the history of the first municipal institution of secondary education in the city of Fortaleza, explaining relevant aspects of education at the time, as well as the political and civil agents that gave life to the Institution. The importance of this research consists in not only giving due value to the legacy of this institution, which is configured as a symbolic device for the democratization and expansion of teaching, but also in arousing reflection on the role it has played, for 68 years, in history and memory, of Education in Fortaleza.